A Brain Tumor Mimicking Brain Abscess - Achmad Harun Muchsin; Rachmat Faisal Syamsu; Armanto Makmun (UMI Medical Journal, 2017)
A brain tumor could be mimicking brain abscess in some cases. Not just in imaging but also both of has a similar symptoms, physician must anamnesis properly and run several tests. A brain abscess is an intraparenchymal collection of pus. The incidence of brain abscesses is approximately 8% of intra-cranial masses in developing countries and 12% in the western countries. In this case, we reports a male patient with gradually left hemiplegia, left deviation of tongue, left hemifacial paresis, and visual hallucination and psychological disturbance. Initial imaging showed the possibilities of space occupying lessions (SOL) with suspect to Astrocytoma. But, based from the history taking, there is bad habit of oral hygiene, that the patient usually sticks his gum with tooth stick and after confirmation from second head CT scan with contrast enhancement, confirmed right cerebral abscess with perifocal oedem. After 2 weeks empirical antibiotic therapy, there is significant clinically improvement. But, after we confirm with second Head CT scan with contrast enhancement, there is a very minimum decreased size of the abscess lesion, so surgical drainage is indicated. We collect Xanthochromic liquid from surgical drainage (not purulent), and from microscopic evaluation inflammation lesion confirmed. But by microbiological culture, there is no growth of aerobic bacteria from drainage liquid culture, we assume because of empirical antibiotic therapy was started before the microbiological culture test. After surgical drainage, there is no complication, and clinical become more improve.